Study on oil pilot circuit of adaptive hydraulic drive of tool advance in mobile drilling machine - V. S. Sidorenko; V. I. Grishchenko; S. V. Rakulenko; M. S. Poleshkin; D. D. Dymochkin (Advanced Engineering Research, 2019)
Introduction. An adaptive hydraulic drive of the tool advance in a mobile drilling machine is studied on the example of the URB-2.5 installation. A typical technological cycle of the mobile drilling machine is considered; the performance criteria are defined. An original design of the adaptive hydraulic drive is proposed on the basis of the analysis. Adaptation of the hydraulic drive of the tool advance is carried out using an adjustable volumetric hydraulic motor with a hydraulic control circuit under discontinuous loads on the tool during the drilling process.Materials and Methods. Through a preliminary computational experiment in the Matlab Simulink program, the following parameters of the control loop devices were determined: a hydromechanical sensor and a hydraulically controlled valve, on the basis of which the experimental setup was implemented. The performed multifactor experiment allowed identifying the processes in the original hydraulic control circuit of the hydraulic motor under various modes of tool loading.Research Results. The kinematic and power characteristics of the hydromechanical system of a mobile drilling rig, the hydraulic control effect on the settings of the hydraulic control circuit devices were obtained and determined. The results enabled to specify the rational ranges of the hydromechanical system operation for a typical work cycle.Discussion and Conclusions. The results obtained can be used to create hydraulic systems of new drilling machines with various characteristics. The application of the developed techniques of research and processing of their results will reduce the time and costs involved in designing adaptive hydraulic systems for mobile technological machines, creating prototypes and conducting commissioning procedures.